Numerical Analysis of Sedimentation in Open Channels Using Computational Fluid Dynamics - Putra, Yoga Satria; Noviani, Evi; Hasanuddin, Hasanuddin; Kurnia, Elsa; Christy, Maria Citra Puella (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
This study investigates sedimentation in open channels utilizing Computational Fluid Dynamics (CFD). The validation indicates a strong agreement between the simulation and the reference data. Flow velocity substantially decreases in the branched channel post-bifurcation. Similarly, at a 90o bend, there is a notable drop in flow velocity after the curve. A vortex forms in areas where the velocity decreases. Sedimentation prediction can be achieved by observing these velocity reductions in specific channel sections. In the branched channel, low velocities and localized water eddies are found after the bifurcation point. In a channel with a 90o bend, the velocity diminishes on the inner side of the curve, with vortices forming, acting as potential sediment traps. This study highlights the utility of CFD as an effective method for enhancing the understanding of sedimentation processes in river systems.